ŠIMÁNĚ 2017 - Editorial, Foreword (Acta Polytechnica CTU Proceedings)
Nuclear science and technology have a long history within the Czechoslovakia. Even though the Czech Republic and Slovakia have been separated since 1993, wide cooperation on different levels including education and research still exists. In order to support cooperation and good relations between Czech and Slovak students, the organizing committee decided to hold the 2nd student conference on nuclear engineering - Šimáně 2017. The conference is named after professor Šimáně, who graduated at the Dr. Edvard Beneš Technical University in Brno. During his early career, he had the opportunity to work with Fréderic Joliot-Curie at College de France. Later, he significantly contributed to the foundation of the nuclear science, industry and education in the Czechoslovakia. He became the first employee of the Institute of Nuclear Physics at the Czechoslovakian Academy of Science, later he became the first director of the Nuclear Research Institute in Řež. Professor Šimáně was well established even on the international level. He was a director at the Joint Institute of Nuclear Research in Dubna or a division director at the International Agency for Atomic Energy. His work was also significantly connected with our faculty where he acted as Dean from 1967 to 1972. The main objective of the conference is to provide an opportunity for BSc., MSc. and Ph.D. students of nuclear-oriented study programmes to publish and present their scientific results achieved during their university studies. Furthermore, it should give the participants experience in the field of presenting their own research, writing scientific papers and also broaden their knowledge throughout the related fields. The organizing committee would like to thank all participants for their presentations and also to the CTU in Prague for funding this student conference. The committee also hopes that the work achieved and presented will fulfill the heritage of professor Čestmír Šimáně. Scientific Committee: Milan Štefánik Martin Ševeček Martin Cesnek Local Organizing Committee: Adam Kecek Vojtěch Caha Martin Cesnek Filip Fejt Martin Ševeček Milan Štefánik Peer-review proces guarantee: Milan Štefánik Language editing guarantee: Martin Ševeček Guest editors:  Martin Ševeček Martin Cesnek